The Influence of Digital Capability on Competitive Advantage at MAN 1 South Konawe - Erdiyanti; Wahyuningsih, Sri; Syamsuddin (IAIN KENDARI, 2026)
This study examines the influence of digital capability on competitive advantage at MAN 1 South Konawe. The objectives are to determine the condition of digital capability, the condition of competitive advantage, and the influence of digital capability on competitive advantage. This is a quantitative study using a survey method. The population in this study consists of 40 teachers, with the entire population serving as the sample. The data collection technique used in this study involves a questionnaire for teachers. The data analysis technique employed in this study is descriptive analysis, including prerequisite tests (normality and linearity) and hypothesis testing. The results of the study indicate that the alternative proposed hypothesis is accepted because the hypothesis test results show that the digital capability variable has a positive and significant effect on competitive advantage at MAN 1 South Konawe with a value of 43.7%. This means that good digital capability results in a 43.7% increase in competitive advantage at MAN 1 South Konawe.